Medical Gas Plasma Technology Combines with Antimelanoma Therapies and Promotes Immune‐Checkpoint Therapy Responses - Lea Miebach; Gabriella Melo‐Zainzinger; Eric Freund; Ramona Clemen; Alessandra Lourenco Cecchini; Sander Bekeschus (Advanced Science, 2023)
Abstract Strategies to improve activity and selectivity are major goals in oncological drug development. Medical gas plasma therapy has been subject to intense research in dermatooncology recently. Based on partial gas ionization, this approach is exceptional in generating a variety of reactive oxygen species simultaneously that can be applied locally at the tumor side. It is hypothesized that combined gas plasma treatment can potentiate drug responses in the treatment of melanoma. Using a plasma jet approved as medical device in Europe, a systematic screening of 46 mitochondria‐targeted drugs identifies five agents synergizing in vitro and in vivo. Increased intratumoral leucocyte infiltration points to immunomodulatory aspects of the treatment, motivating to investigate responses to immune checkpoint blockade in combination with plasma. Tumor growth is monitored based on bioluminescent imaging, and single‐cell suspensions are retrieved from each tumor to characterize tumor‐infiltrating leucocytes using multicolor flow cytometry. Gene expression profiling is done using a validated NanoString panel targeting 770 genes specifically designed for immuno‐oncological research. Cell type abundancies are characterized from bulk RNA samples using the CIBERSORT computational framework. Collectively, the results indicate that local application of medical gas plasma technology synergizes with mitochondria‐targeted drugs and anti‐PD1 checkpoint therapy in treating melanoma.